Imagining biofuels: building agricultural supply chains in the UK: a comparison of UK policy expectations with on-farm perspectives - Helliwell, Richard (2017)
This thesis aims to drawn on theoretical insights from science and technology studies and rural studies literatures to interrogate the potential agricultural system and on-farm changes required for developing lignocellulosic biofuel supply chains in the UK. Previous work has largely examined first generation, food based biofuels, with limited focus on the prospects for lignocellulosic technologies. Likewise policy identifies a number of challenges for lignocellulosic biofuels, commercial, technical, and sustainability, that require policy solutions. However, biofuels straddle the agricultural-energy sectors. The deployment of these technologies will demand the adoption of certain practices and crops by farmers, as well as broader changes to agricultural systems. These important components for delivering lignocellulosic biofuels require examination which has so far been limited.